THE EFFECT OF LEMON AROMATHERAPY ON REDUCING DYSMENORRHEA PAIN AMONG FEMALE STUDENTS AT SMP NEGERI 1 SIMPANG TIGA, ACEH BESAR REGENCY - Amiratut Diana; Yadi Putra; Mansuriza (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Menstrual pain or dysmenorrhea can cause disruption of daily activities in teenage girls, lessen concentration, and even affect their academic achievement. Lemon aromatherapy is a non-pharmacological method used to reduce dysmenorrhea pain by giving relaxation and analgesic effects with its active compounds, such as limonene and linalool. Based on the data from the World Health Organization (WHO), around 90% of women experience dysmenorrhea, and 10–15% of them suffer from severe dysmenorrhea that requires intervention. This study aims to determine the effect of lemon aromatherapy in reducing the level of dysmenorrhea pain among girls. This study was a quantitative research with a quasi-experimental approach using a one-group pretest-posttest design. The population was all seventh and eighth-grade female students of SMP Negeri 1 Simpang Tiga, Aceh Besar, who experienced dysmenorrhea. A total of 15 respondents were selected using purposive sampling. The study was conducted from May 29 to June 21, 2025. The intervention was carried out by giving lemon aromatherapy on the first to third day of menstruation, once a day intake for about 15 minutes. The pain level was assessed using the Numerical Rating Scale (NRS). The data were analyzed using the Paired Samples T-Test. The results showed that most respondents experienced moderate pain (93.3%) before receiving the treatment, and a small proportion experienced severe pain (6.7%). After receiving lemon aromatherapy, the pain level decreased to mild pain (46.7%) and moderate pain (53.3%). The mean pain score before intervention was 3.07 and decreased to 2.53 after intervention, with a difference of 0.54. The statistical analysis obtained a p-value of 0.001 (p < 0.05), indicating that there was a significant effect of lemon aromatherapy on reducing dysmenorrhea pain. Thus, based on the findings, this study recommends that teenage girls use lemon aromatherapy as an alternative independent treatment to reduce menstrual pain complaints.